1979
DOI: 10.1021/j100471a022
|View full text |Cite
|
Sign up to set email alerts
|

Infrared chemiluminescence studies of the hydrogen + chlorine fluoride reaction. Energy disposal and branching ratios

Abstract: Publication costs assisted by the National Science FoundationInfrared chemiluminescence under arrested relaxation conditions has been used to study the HF and HCl formation channels of the H + C1F reaction at 300 K. From the relative infrared emission intensities the ratio of channels was determined as 4.4 in favor of HC1, the less exoergic channel. The energy disposal is ( / " ) H a = 0.42, (~R ) H C I = 0.14, (~T ) H c~ = 0.44, and (f\-)HF = 0.57, (~R ) H F = 0.10, (fT)HF = 0.33. The rotational distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 5 publications
8
24
0
Order By: Relevance
“…16 For reactions of H atoms with IX compounds (X ¼ Cl=F), an H migration step following adduct formation has long been recognized. [17][18][19] In the present study infrared chemiluminescence from HCl(v) was observed from the H þ CH 2 ClI reaction, and an adduct seems to facilitate HCl formation. At least two channels are possible: The thermochemistry is not well established, but the enthalpies of reaction (in kJ mol À1 ) based upon our thermochemical estimates, vide infra, are given in parentheses.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…16 For reactions of H atoms with IX compounds (X ¼ Cl=F), an H migration step following adduct formation has long been recognized. [17][18][19] In the present study infrared chemiluminescence from HCl(v) was observed from the H þ CH 2 ClI reaction, and an adduct seems to facilitate HCl formation. At least two channels are possible: The thermochemistry is not well established, but the enthalpies of reaction (in kJ mol À1 ) based upon our thermochemical estimates, vide infra, are given in parentheses.…”
Section: Introductionsupporting
confidence: 49%
“…The distribution is nearly flat for v ¼ 1-3 and it is similar to the HX(v) distribution observed from the H þ IX reactions. [17][18][19] For comparison, the HX distributions from H þ ICl, NFCl 2 , CF 3 O and CF 2 Cl are included in Table 1. The H þ CF 2 Cl and CF 3 O reactions give stable molecules before unimolecular HX elimination occurs.…”
Section: Iii2 Hclmentioning
confidence: 99%
“…We note parenthetically that the observation of high rotational excitation in the products of the gas phase reaction, to which we have referred earlier, does not contradict the insertion mechanism because Monte Carlo simulations of the o('D) + HCl reaction using a statistical model suggest (60) that the high OH rotational excitation arises from angular momentum constraints and has no unique dynamical origin. It has been noted that the energy partitioning of both the ground state and excited state reactions resembles that of the direct abstraction reaction of F with HBr (34,61). The observation, however, of a marked propensity for production of the II(A') A component in the OH product of the o('D) + HCI reaction (13) implies that the half-filled IT orbital of OH lies preferentially oriented in its rotational plane and remains in the plane of the dissociating triatomic complex.…”
Section: Angular Distrib~ltionsmentioning
confidence: 99%
“…leads to the study of the rate constant branching ratio (k 1 /k 2 ) for each possible interhalogen molecule and its comparison with the study of the reactions with di †erent XY and (or X 2 molecules. Moreover, the hydrogen exchange reaction Y 2 ) between a halogen Y and the HX molecule is a reaction that involves as reactants the products of reactions (1) and (2). These three reactions close the triangle of connections among the three asymptotic regions of the ground potential energy surface (PES) 2A@ of the HXY system.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have studied the three exoergic reactions involved in the HClF system (X \ Cl, Y \ F). In previous studies on reactions (1) and (2) using infrared chemiluminescence techniques, there have been measured detailed rate constants k(v@) and k(v@, J@) at 300 K.1h3 Microscopic branch-ing has also been observed in reaction (2) but not in reaction (1). Infrared chemiluminescence studies of reaction (3) have also furnished detailed rate constants k(v@) and k(v@, J@) at 300 and 1700 K ;4 k(v \ 0, 1, 2), k(v \ 1, J), k(v@ o v) and other detailed rate constants have also been reported in the same work (primed variables refer to the products vibrational and rotational quantum numbers).…”
Section: Introductionmentioning
confidence: 99%